Technology of forming the foreign language communicative culture of students of technical universities based on the study of styles and trends of world literature. Ch. 7 - Saienko, Nataliia; Ptushka, Anastasiia; Borzenko, Oleksandra; Nosyryeva, Olena; Krasnopyorov, Petro (Technology Center PC, 2025)
Strengthening the potential of international integration of graduates of Ukrainian technical universities and their effective adaptation to the socio-cultural environment of industrialised countries requires the development, validation and implementation of educational technologies for training future specialists in such important for the national economy specialities as mechanical engineering, energy, chemical engineering, civil engineering, economics, ecology, transport, IT technologies. Intercultural communicative competence is formed in the process of studying a foreign languages and multicultural education. It is necessary to modernise the existing curricula for the study of foreign languages and cultures by introducing innovative elements that increase the level of preparedness of future professionals for international economic and technological interaction. A developed communicative culture presupposes a qualitative knowledge of languages, the achievement of which is to some extent hindered by students’ poor understanding of stylistic norms of language, which are not taught in non-philological universities, and which is a frequent cause of errors in oral and written communication by future graduates. The study attempts to form stylistic skills of students of a technical university, the presence of which means the ability to clearly and distinctly express their thoughts, adhering to stylistic norms, to select and adequately use various stylistic means of the language in accordance with the communication situation. The development of stylistic skills was carried out on the material of English-language fiction, which is considered a rich resource for carrying out stylistic analysis of texts, developing students’ communicative competence, and increasing their general cultural level.
Keywords: students of technical universities; foreign language; stylistic skills; fiction; https://doi.org/10.15587/978-617-8360-15-3.ch7